Recent Publications upon Economics (Quarterly Journal of Economics, 1906)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 20, Issue 2, February 1906, Pages 304–321, https://doi.org/10.1093/qje/20.2.304 Published: 01 February 1906